1990
DOI: 10.1177/088307389000500319
|View full text |Cite
|
Sign up to set email alerts
|

Rhythmic Coma in Children

Abstract: We describe a syndrome of rhythmic coma in children that consists of an invariant, nonreactive, diffuse cortical activity of a specific frequency, such as alpha, beta, spindle, or theta, recorded from a comatose child. We report 11 cases of children who were found to be in rhythmic coma during their acute illnesses. Their ages ranged from 2 to 15 years, and their diagnoses included encephalitis, head trauma, seizures, near drowning, brain tumors, stroke, and metabolic derangements. The specific frequency of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

1993
1993
2017
2017

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 22 publications
1
9
0
Order By: Relevance
“…Kaplan et al [2] in a meta-analysis of 36 patients with alpha coma found that 11 of these had concomitant beta (> 13 Hz) activity. Horton et al [10] found that EEG patterns of coma are more varied in children. In our patient, the predominant frequency was 8−9 Hz.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Kaplan et al [2] in a meta-analysis of 36 patients with alpha coma found that 11 of these had concomitant beta (> 13 Hz) activity. Horton et al [10] found that EEG patterns of coma are more varied in children. In our patient, the predominant frequency was 8−9 Hz.…”
Section: Discussionmentioning
confidence: 99%
“…A repeat 16-channel EEG on day 16 showed persistence of intermittent diffuse alpha activity with a mixture of other frequencies. EEG monitoring by cerebral function analyzing monitor for 48 hours (day 16 to day 18) showed prominent activity in the alpha frequency band (8)(9)(10)(11)(12)(13). No paroxysmal activity was noted in either routine EEG or in the cerebral function-analyzing monitor monitoring.…”
Section: Case Reportmentioning
confidence: 95%
See 1 more Smart Citation
“…18-4). [93][94][95] If the pattern can be interrupted by the application of external stimuli, the prognosis is considered better than if the pattern is unreactive. [93][94][95] If the pattern can be interrupted by the application of external stimuli, the prognosis is considered better than if the pattern is unreactive.…”
Section: Spindle Comamentioning
confidence: 99%
“…92 It has been reported in traumatized children as well as adults. Horton and colleagues 95 found that the frequency of the invariant, nonreactive, diffuse cortical activity seen in children with coma was not confined to a single frequency and proposed the term rhythmic coma as a unified concept for alpha, beta, spindle, and theta coma in children. Horton and colleagues 95 found that the frequency of the invariant, nonreactive, diffuse cortical activity seen in children with coma was not confined to a single frequency and proposed the term rhythmic coma as a unified concept for alpha, beta, spindle, and theta coma in children.…”
Section: Spindle Comamentioning
confidence: 99%